XI. VE XIII. YÜZYILLARDA TÜRK-ERMENİ İLİŞKİLERİ - SERTEL, SAVAŞ (Fırat Üniveristesi, 2006)
Türk-Ermeni ilişkileri iki boyutta ele alınabilir. Bunlardan ilki siyasi boyuttur. Siyasiboyutta yapılan savaşlar, antlaşmalar, ittifaklar, siyasi evlilikler, toprak paylaşımı, idariyapılar, veraset ve 1071 Malazgirt Zaferinden sonra yoğunlaşan Türk-Ermeni ilişkileri dahiledilebilir. Haçlı seferlerinde, Haçlılara yardım eden Ermeniler, daha sonra Haçlılarınzulmünden bıkıp, Türklerin yanında yer almışlardır.Türk-Ermeni ilişkilerinin ikinci boyutu olan sosyal boyutta ise ticaret, sanat, ziraat,sanayi vs. konularda bilgi ve maddi alışverişler olmuştur. Bunun yanı sıra Kültürel alışverişleryaşanmıştır. Türk ve Ermeni dil ve edebiyatında, sanatında, kültüründe, geleneklerinde veyaşayış tarzında geniş çapta etkileşimler yaşanmıştır.Bu dönemde Anadolu'da Selçuklu Türkleri, Ermenilere hakim konumda olduğundankültürel yönden etkileyen taraf da Türklerdi. Bundan dolayıdır ki, Ermenice içerisinde enfazla kelime barındıran dillerden biri de Türkçedir.Sonuç itibariyle göçlerin, savaşların, istilaların, paylaşımların yaşandığı bir coğrafyadabir araya gelen bu iki millet, olumlu ya da olumsuz olarak birbirini etkilemiştir. lişkilerzaman zaman savaşlar şeklinde olmuştur.Anahtar Kelimeler: Ermeni, ttifak, Savaş, Türk, Zafer

Turk-Armenian relations can be discussed in two different dimensions.One of them is its political dimension. We can consider wars, pacts, alliances, politicalmarriages, sharing of lands, managerial configuration, inheritance etc. in this political side.Turk-Armenian relations became more frequent after 1071 Malazgirt victory and continued aswar, pacts and temporary alliances. Armenians helped Crusades while they were attackingTurks but after they get bored with cruelty of Crusades, they helped Turks.We can consider trade, art, agriculture, industry, etc. in the social dimension of Turk-Armenian relations. This is the other dimension of relations and two nations had a trade ofknowledge and materials. Nevertheless cultural trades were lived. In both Turk and Armenianside there had been a great interaction in language, literature, art, culture, tradition and lifestyle.In this term, Turkish Seljuk was supreme in Anatolia and Turkish side had affectedArmenians more because of their dominant position. Because of this fact, in Armenianlanguage, there are a lot of Turkish words.In conclusion, these two nations came together in a geography which had migrations,wars, invasions, sharing; and affected to each other in a positive or negative way. Relationswere sometimes about war and sometimes about alliance.Key Words: Armenian, Alliance, War, Turk, Victory
Turk-Armanian relations between XI. and XIII. centuries
Keywords: Tarih